(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
This research focuses on the urban flora components of Kiev megapolis rarity, which includes 151 species of vascular plants (15 % аboriginal fraction), with international, national and regional sozological status. Based on biomorphological analysis of the results it was revealed that among the main components of the rarity biomes herbaceous polycarpic are predominant (132; 87,4 %); among the types of root systems – plant with adventitious roots (119; 78,8 %); the aerial shoots – shortened rosette (92; 61,0 %); underground shoots – short- and elongated rhizome (89; 59,0 %) species. By the nature of vegetation summer vegetation (91; 60,3 %) and summer and winter (35; 23,2 %) species are dominant. The predominant species are monocentric biomorphs (71; 47,0 %). In ecomorphs spectrum among klimamorf geophytes (54; 35,8 %) and hemicryptophytes (50; 33,1 %) are dominant. Analysis of biomorfological features of rare species allowed to establish their adaptability to a wide range of ecological conditions, coenotic suburbanzone of Kiev megapolіs.